Food safety, risk intelligence and benchmarking - Charlebois, Sylvain (Chichester, United Kingdom John Wiley & Sons, 2017)
This book comprehensively argues for more future benchmarking between nations. Since the initial food safety benchmarking report was published in 2008, the sharing of data and protocols among nations has dramatically increased. It was intended to identify and evaluate common elements among global food safety systems.
Includes bibliographical references and index.
Keywords: Food -- Safety measures; Food -- Quality; Food industry and trade -- Securtiy measures -- International cooperation; Food industry and trade -- Risk management; Food adulteration and inspection; Benchmarking (Management)